Website Quality and Social Media Influencers as Key Drivers of Online Purchase Intention in Thanksinsomnia - Amanah, Dita; Harahap, Dedy Ansari (Klabat Journal of Management, 2025)
Analyzing online purchase intention in Thanksinsomnia Indonesia is crucial as it provides critical insights into consumer behavior in an increasingly digital environment. Online purchase intention reflects a consumer’s likelihood to make a purchase, which ultimately has a direct impact on revenue and business growth. By understanding the factors that influence online purchase intention, such as website quality, user experience, and the influence of social media influencers, companies can optimize their digital marketing strategies. In addition, this analysis helps in identifying potential barriers that may prevent consumers from making a purchase, allowing companies to make necessary improvements to increase conversions. In the context of intense competition in the e-commerce market, a deep understanding of online purchase intention also allows Thanksinsomnia to remain relevant and competitive, while building long-term relationships with customers. This article examines the influence of website quality and social media influencers on online purchase intention. This study uses a quantitative approach with a survey method involving 200 respondents, who are active consumers of the brand. The data were analysed using multiple linear regression to test the relationship between the independent and dependent variables. The results showed that website quality has a significant and positive influence on online purchase intention, while the influence of social media influencers also contributes significantly to increasing online purchase intention. In conclusion, both website quality and social media influencers are important factors in shaping consumers' online purchase intentions. These findings provide practical implications for brand managers in optimizing their digital strategies to increase customer engagement and conversion.